2022
DOI: 10.1016/j.cmi.2021.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and microbiology of respiratory and bloodstream bacterial infection in patients with COVID-19: living rapid review update and meta-regression

Abstract: Predictors and microbiology of respiratory and bloodstream bacterial infection in patients with COVID-19: living rapid review update and metaregression Clinical Microbiology and Infection, https://doi.org/10.1016/j.cmi.2021.11.008. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 176 publications
6
50
0
3
Order By: Relevance
“…As expected, the presence of pressure ulcers depends on the duration of intubation, as the longer the period of invasive mechanical ventilation the higher the risk. Likewise, ICU setting and mechanical ventilation are risk factors for development of secondary bacterial infections [ 23 ]. In turn, such infections can result in a prolonged period of mechanical ventilation and ICU stay, and an increased mortality rate [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the presence of pressure ulcers depends on the duration of intubation, as the longer the period of invasive mechanical ventilation the higher the risk. Likewise, ICU setting and mechanical ventilation are risk factors for development of secondary bacterial infections [ 23 ]. In turn, such infections can result in a prolonged period of mechanical ventilation and ICU stay, and an increased mortality rate [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the baseline characteristics in the infected and control groups that may be related to infection [21][22][23], including gender, age, days of hospitalization, clinical stage, number of admissions, surgery, intraoperative bleeding, chemotherapy, radiotherapy, and other characteristics. Our study revealed that hospitalization days ≥7 days, number of days ≥7 days, surgery, and chemotherapy were the independent risk factors for E. coli BSI.…”
Section: Discussionmentioning
confidence: 99%
“…Bradley J Langford, BScPhm, PharmD 1,2 Miranda So, BScPhm, PharmD, MPH 3,4,5 Valerie Leung, BScPhm, MBA 1,6 Sumit Raybardhan, BScPhm, MPH 7 Jennifer Lo, BScPhm, PharmD 8 Tiffany Kan, BScPhm, PharmD 6 Felicia Leung, HBSc 4 Nick Daneman, MD, MSc 1,4,8,10,11 Derek R MacFadden, MD, ScD 12 Jean-Paul R Soucy, MSc 9…”
Section: 'Predictors and Microbiology Of Respiratory And Bloodstream ...mentioning
confidence: 99%
“…To the Editor, We thank the authors for their interest and comments regarding our publication in CMI [1]. Given the vast amount of literature published on the topic of co-infections and secondary infections in COVID-19, and the heterogeneity in publication quality, methodological approach, and data reporting strategies, it was necessary to make some assumptions regarding whether studies met inclusion criteria.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%